Commodity Price Cycles : The Perils of Mismanaging the Boom - Sosa, Sebastian (IMF Working Papers; Working Paper, 2011)
Commodity-exporting countries have significantly benefited from the commodity price boom of recent years. At the current juncture, however, uncertain global economic prospects have raised questions about their vulnerability to a sharp fall in commodity prices and the policies that can shield it from such a shock. To address these questions, this paper takes a long term (4 decade) view at emerging markets' commodity dependence, the history of commodity price busts and the role of policies in mitigating or amplifying their economic impact. The paper highlights the stark difference in trends between Latin America - one of the most vulnerable regions given its high, and rising, commodity dependence - and emerging Asia - which has evolved from being a net exporter to a net importer of commodities in the last 40 years. We find evidence, however, that while commodity dependence is an important ingredient, a country's ultimate degree of vulnerability to commodity price shocks is to a great extent determined by the flexibility and quality of its policy framework. Policies in the run-up of sharp terms-of-trade drops - especially when those are preceded by booms - play a particularly important role. Limited exchange rate flexibility, a weak external position, and loose fiscal policy tend to amplify the negative effects of these shocks on domestic output. Financial dollarization also appears to act as a shock "amplifier.".